Sensitive Skin in Children - Laurent Misery; Charles Taïeb; Emilie Brenaut; Flavien Huet; Claire Abasq-Thomas; Michèle Sayag; Christine Bodemer (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)